Belarus as a sustainable medical tourist destination - Camlioglu, Vera. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
In recent decades, there has been a rapid growth in the medical tourism market in a number of countries. In this regard, the importance of studying the experience of the development of this phenomenon in various contexts increases. This research aims to investigate the medical tourism system in Belarus, a country where this industry is developing in the context of a universal healthcare system with a dominant public sector that accounts for a large part of medical tourists. Covering the experience of a destination with such a particular context contributes to the literature that has previously looked primarily at countries where in contrast the private sector plays an important role in providing medical services to tourists. This research presents the supply stakeholders’ vision of the current situation in the field of medical tourism in Belarus and highlights some features and differences adherent to the system and development scenario. The study is carried out within a sustainability perspective and showcases the areas of medical tourism in Belarus that meet or contradict the principles of sustainable development. The data was collected through in-depth semi structured interviews with main supply-side stakeholders of medical tourism in Belarus that were selected by using judgmental and snowball sampling methods. Descriptive qualitative approaches such as thematic analysis and content analysis were applied for the examination of the interview data. Several unique aspects in the development and structure of medical tourism in Belarus are highlighted, leading to theoretical and practical implications.
Keywords: Medical tourism -- Belarus.